Cv avero employee payment transformation: website-based information system design for optimal efficiency - Rosmalina, Rosmalina; Nistrina, Khilda; Mustopa, Aris (Institute of Computer Science (IOCS), 2024)
In an endeavor to enhance operational efficiency and stay abreast of swift business advancements, CV. Avero Indonesia recognized the imperative to integrate information technology into its payroll system. Presently, the company relies on partially computerized methods employing Microsoft Excel and Microsoft Word for managing attendance records, generating payroll reports, and issuing pay slips. However, this approach introduces constraints such as manual salary calculations, computation of team and individual bonuses, overtime pay, and the generation of reports. To address this challenge, the objective of this research is to develop an integrated payroll information system based on a website platform. Following the waterfall method, the research encompasses phases such as definition, requirements analysis, system design, implementation, and testing. The outcome is a payroll information system equipped with features including division management, position tracking, employee data management, attendance recapitulation, overtime tracking, individual and team target setting, as well as comprehensive salary reports, attendance records, overtime details, and pay slips. This system aims to minimize reliance on Microsoft Excel, thereby augmenting operational efficiency and facilitating better control over employee performance. Furthermore, the data processed through this system can be utilized for future company development, ensuring data integrity, and supporting the rapid growth of the business. Through the implementation of this innovative solution, CV. Avero Indonesia positions itself to sustain competitiveness and success within a dynamic business environment